Thirty-Day Readmissions After Left Ventricular Assist Device Implantation in the United States: Insights From the Nationwide Readmissions Database. (March 2018) - Agrawal, Sahil; Garg, Lohit; Shah, Mahek; Agarwal, Manyoo; Patel, Brijesh; Singh, Amitoj; Garg, Aakash; Jorde, Ulrich P.; Kapur, Navin K.
Abstract : Background: Early readmissions contribute significantly to heart failure–related morbidity and negatively affect quality of life. Data on left ventricular assist device (LVAD)–related 30-day readmissions are scarce and limited to small studies. Methods and Results: Patients undergoing LVAD implantation between January 2013 and November 2014 who survived the index hospitalization were identified in the Nationwide Readmissions Database. We analyzed the incidence, predictors, causes, and costs of 30-day readmissions. Of 2510 LVAD recipients, 788 (31%) were readmitted within 30 days. Length of index hospitalization ≥31 days (hazard ratio [HR], 1.26; 95% confidence interval [CI], 1.07–1.50) and female sex (HR, 1.19; 95% CI, 1.01–1.42) were associated with a higher risk of 30-day readmission, whereas private insurance (HR, 0.83; 95% CI, 0.70–0.99), pre-LVAD use of short-term mechanical circulatory support (HR, 0.53; 95% CI, 0.29–0.98), and discharge to a short-term hospital facility (HR, 0.41; CI, 0.21–0.78) were associated with a lower risk. Cardiac causes accounted for 23.8% of readmissions: heart failure (13.4%) and arrhythmias (8.1%). Noncardiovascular causes accounted for 76.2% of readmissions: infection (30.2%), bleeding (17.6%), and device-related causes (8.2%). Mean length of stay for readmission was 10.7 days (median, 6 days), and average hospital cost per readmission was 34 948±2457. Conclusions: Early readmissions are frequent after LVAD implantation even in contemporary times. Preimplant identification of high-risk patients, and a protocol-driven follow-up using a multidisciplinary approach will be needed to reduce readmissions and improve outcomes. Abstract : Supplemental Digital Content is available in the text.